Bretherick's Handbook of Reactive Chemical Hazards - Bretherick, Leslie; Urben, Peter (Butterworth-Heinemann [Imprint] San Diego : Elsevier Science & Technology Books., 1999)
Annotation 'Bretherick' is widely accepted as the reference work on reactive chemical hazards and is essential for all those working with chemicals. It includes every chemical for which documented information on reactive hazards has been found. The text covers over 5000 elements and compounds and as many again of secondary entries involving two or more compounds. One of its most valuable features is the extensive cross referencing throughout both sections which links similar compounds or incidents not obviously related. The sixth edition has been completely updated and revised by Peter Urben and contains documented information on hazards and appropriate references up to 1999 Volume 1 is devoted to specific information on the stability of the listed compounds, or the reactivity of mixtures of two or more of them under various circumstances. Each compound is identified by an UPAC-based name, the CAS registry number, its empirical formula and structure. Each description of an incident or violent reaction gives reference to the original literature. Each chemical is classified on the basis of similarities in structure or reactivity, and these groups are listed alphabetically in Volume 2. The group entries contain a complete listing of all the compounds in Volume 1 assigned to that group to assist cross referral to similar compounds. Volume 2 also contains hazard topic entries arranged alphabetically, some with lists. Appendices include a fire related data table for higher risk chemicals, indexes of registry numbers and chemical names as well as reference abbreviations and a glossary. Now Available Online Bretherick s Handbook of Reactive Chemical Hazards is now available online through ChemVillage. For more information please contact the customer services department at eicustomersupport@elsevier.com Features and Benefits: . " Regular Updates existing data updated and new data added on a regular basis. " Extensive Cross Referencing - helps your research by linking compounds or incidents often not obviously related. " Affordable flexible pricing options. " Structure Searches amongst various text search options, this database offers structure searches using MDL Chime and MDL ISIS/Draw plug-ins (free access). " Online Availability rapid delivery of information you need for your safety research. " Numerous compounds and elements over 5000 compounds and elements are covered. This number is constantly increasing as the information is updated.
Scholarly & Professional
Keywords: Hazardous substances -- Handbooks, manuals, etc; Chemicals -- Safety measures -- Handbooks, manuals, etc; Electronic books